Prenatal Sonographic Features of Fetuses in Trisomy 13 Pregnancies (II) - Chih-Ping Chen (Elsevier, 2009)
Prenatal ultrasound is a powerful tool for detecting structural abnormalities in fetuses in trisomy 13 pregnancies. This article provides a comprehensive review of the prenatal sonographic features of trisomy 13 in the second and third trimesters, including holoprosencephaly, brachycephaly, microcephaly, Dandy-Walker complex and posterior fossa abnormalities, ventriculomegaly, neural tube defects, facial cleft, and micrognathia.